I'm given an absolutely continuous stochastic variable $U$, with the probability density function $f_{U}$ given by; $$ f_{U}\left(u\right) = \left\{ \begin{array}{ll} 2u & \text{ if } u \in \left] 0,1 \right[ \\ 0 & \text{ otherwise.} \end{array} \right. $$

My task is now to derive the probability density function for $X = e^{U}$. I've tried different approaches, however I'm unable to get the expected result of; $$ f_{X}\left(x\right) = \left\{ \begin{array}{ll} \frac{2 \cdot \ln\left(x\right)}{x} & \text{ if } x \in \left] 1,e \right[ \\ 0 & \text{ otherwise.} \end{array} \right. $$


Found another exercise alike this one (which seems simpler)

I'm given an stochastic variable $Y \sim R\left(0,1\right)$, with the probability density function $f_{Y}$ given by; $$ f_{Y}\left(y\right) = \left\{ \begin{array}{ll} 1 & \text{ if } y \in \left]0,1\right[ \\ 0 & \text{ otherwise.} \end{array} \right. $$

My task is now to derive the probability density function for $Z = Y^{3}$. Again without any luck I've tried different approaches, and I'm unable to reach the expected result of; $$ f_{Z}\left(z\right) = \left\{ \begin{array}{ll} \frac{1}{3} \cdot z^{-\frac{2}{3}} & \text{ if } z \in \left]0,1\right[ \\ 0 & \text{ otherwise.} \end{array} \right. $$


So far I've been able to determine the correct intervals, using the method @DilipSarwate.

After I figured, that I was integrating, rather than differentiating (thanks to @JonathanY.), I'm able to get the first exercise, to get the correct answer, the second is however troublesome:

Differentiating $z^{\frac{1}{3}}$ yields $\frac{1}{3} \cdot z^{\frac{2}{3}}$, and not; $\frac{1}{3} \cdot z^{-\frac{2}{3}}$


What should I do in order to reach the correct result (please see discussion on the answer)?

  • $\begingroup$ Differentiating $z^{\frac{1}{3}}$ yields $\frac{1}{3} \cdot z^{\frac{2}{3}}$, and not $\frac{1}{3} \cdot z^{-\frac{2}{3}}$. True or False: For $a \neq 0$, the derivative of $x^a$ is $ax^{a-1}$ ?? $\endgroup$ – Dilip Sarwate Aug 12 '13 at 2:10
  • $\begingroup$ The last statement is true, and I do believe that the differential of $z^{\frac{1}{3}$ is correct, but if this is the case, then my expected result, must be wrong, can you confirm this? $\endgroup$ – Skeen Aug 12 '13 at 13:24
  • $\begingroup$ Another Question: Does $\frac{1}{3} - 1$ equal $\frac{2}{3}$ or does it equal $-\frac{2}{3}$? If the latter, what does setting $a = \frac{1}{3}$ in the statement $$\frac{d}{dz}z^{a} = az^{a-1}$$ yield as the derivative of $z^{\frac{1}{3}}?\ \ $ $\frac{1}{3}z^{-\frac{2}{3}}$ or $\frac{1}{3}z^{\frac{2}{3}}$ as you have repeatedly insisted? $\endgroup$ – Dilip Sarwate Aug 12 '13 at 22:31

First, figure out what values $X = e^U$ can take on in view of the given information about $U$.

Next, write $$F_X(x) = P\{X \leq x\} = P\{e^U \leq x\} = P\{U \leq g(x)\} = F_U(g(x))$$ where you should figure out what $g(x)$ is.

Then, write

$$f_X(x) = \frac{\mathrm d}{\mathrm dx}F_X(x) = \frac{\mathrm d}{\mathrm dx}F_U(g(x)) = f_U(g(x))\frac{\mathrm d}{\mathrm dx}g(x)$$ where once again you need to figure out the derivative of $g(x)$. If the last equality confuses you recall the chain rule for differentiation from basic calculus.

Applying the idea above, if $X$ is uniformly distributed on $(0,1)$, then $Y = X^3$ also takes on values in $(0,1)$ and so for $0 < y < 1$, $Y$ has distribution function $$F_Y(y) = P\{Y \leq y\} = P\{X^3 \leq y\} = P\{X \leq y^\frac{1}{3}\} = F_X(y^\frac{1}{3})$$ and so, $$f_Y(y) = \frac{\mathrm d}{\mathrm dy}F_Y(y) = \frac{\mathrm d}{\mathrm dy} F_X(y^\frac{1}{3}) = f_X(y^\frac{1}{3})\cdot \frac{1}{3}y^{-\frac{2}{3}} = \frac{1}{3}y^{-\frac{2}{3}}, 0 < y < 1.$$ Here we have used the chain rule for differentiation and the facts that $f_X(\cdot)$ has constant value $1$ for arguments in $(0,1)$, and that for $a \neq 0$, $\frac{\mathrm d}{\mathrm dy}y^a = ay^{a-1} = \frac{1}{3}y^{-\frac{2}{3}}$ when $a = \frac{1}{3}$.

  • $\begingroup$ <quote>First, figure out what values $X = e^U$ can take on in view of the given information about $U$.</quote> I've already tried this, by setting $u$ to it's limits (0, and 1), which yields the limits $1$ and $e^{2}$ for $x$ ($e^{2} \neq e$)? $\endgroup$ – Skeen Aug 9 '13 at 12:43
  • $\begingroup$ In ordinary mathematical discourse, the symbol $e$, unless explicitly defined to mean something else, usually means the base of the natural logarithms; and so $e^2 \neq e$. Also, I don't understand how you get that $e^U = e^2$ when $U = 1$. Could you explain further? $\endgroup$ – Dilip Sarwate Aug 9 '13 at 13:16
  • $\begingroup$ The $e$ is indeed the base of natural logarithms. And as for why I got $e^{2}$, that's because I've translated $e^{U}$ to $e^{2*u}$ and then used my values as $u$, should I be using my values for $e^{U}$? $\endgroup$ – Skeen Aug 9 '13 at 16:16
  • $\begingroup$ @Skeen $X = e^U$ and so if $U = 1$, $X = e$, no? Why should the result be any different if you are given additional information to distract you (such as density function of $U$)? $\endgroup$ – Dilip Sarwate Aug 10 '13 at 4:20
  • 2
    $\begingroup$ You've confused derivative with anti-derivative. Differentiate $\ln(x)$ to get $\frac{1}{x}$. $\endgroup$ – Jonathan Y. Aug 11 '13 at 20:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.